Implementation of internal audit recommendations in the Local Government Authorities (LGAs): A case of Dar es Salaam Region - Katuli, Hamadi Ibrahim (Mzumbe University, 2023)
A Research Report Submitted in Partial Fulfilment of the Requirement for Award of Master's Degree of Science in Accounting and Finance of Mzumbe University